Adsorbate-Induced Surface Stress of Methanol Monolayer on Au(III) Surface - Xie, Rong (Asian Journal of Chemistry, 2014)
By using established statistical thermodynamic theory of adsorbate-induced surface stress of adsorption monolayer on metal surface, the surface stress Dg of methanol on Au(III) surface has been calculated. The calculated results indicate that the adsorbed methanol caused compressive surface stress, which is approximately linearly correlated with coverage. Among various terms of intermolecular forces, both the substrate-medicated interaction energy and the induction energy are important to the surface stress.